KESESUAIAN DIAGNOSIS FINE NEEDLE ASPIRATION BIOPSY DENGAN HISTOPATOLOGI POSTOPERATIF PAPILLARY THYROID CARCINOMA DI RUMAH SAKIT RUJUKAN DALAM 3 TAHUN - Sari, Aditya Sita; Kurniasari, Nila; Rahaju, Anny Setijo (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Introduction Thyroid carcinoma is the most common malignancy of the endocrine organ, with papillary thyroid carcinoma being the most common variant. Fine needle aspiration biopsy is still one of cost-effective and less invasive preliminary tests for thyroid lesion. The Bethesda System for Reporting Thyroid Cytopathology uses six categories for thyroid reporting. Methods This was an observational descriptive study with retrospective approach. Data of patients with postoperative histopathology diagnosis papillary thyroid carcinoma was obtained. We then retrieved and reviewed all the previous FNAB slides. All was classified based on Bethesda system for reporting thyroid cytopathology. We considered only patients with histopathology proven diagnosis who underwent FNAB in the same institution. Results 56 cases of FNAB with post-operative histopathology diagnosis papillary thyroid carcinoma were obtained, 34 (62%) of them were diagnosed as papillary thyroid carcinoma, 9 (14.8%) cases were non diagnostic, 10 (17.8%) cases were diagnosed as benign, and 3 (5.3%) cases fell into atypia category. Conclusion Pre-operative FNAB had 36% rate of misdiagnosis, with benign criteria being the most common category. Cases with non-diagnostic category should do repeated FNAB with USG guiding to decrease the possibility of misdiagnosis. Nodule with less than 1 cm size cause the most common misdiagnosis in this study. Most malignant FNAB result has more than 6 cm size.